ANALISIS YURIDIS PEMBATALAN PERWALIAN TERHADAP ANAK OLEH HAKIM PASCA PERCERAIAN (STUDI PUTUSAN NOMOR 400/PDT.G/2011/PN.SBY) - RATI WULANDARI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. H. M. Hasballah Thaib2. Utary Maharany Barus3. Yefrizawati The guardianship concept grounded on the positive law in Indonesia is principally not far different, according to Law No. 23/2002 on Child Protection, Law No. 1/1974 on Marriage, the Compilation of Islamic Laws, Islamic Laws and Adat Law stating that the guardianship is specified only for minors (underage children), although the age limitation of minors is regulated differently among all these laws. A divorce causes parents’ authority into guardianship. Therefore, when a marriage is separated by the judge, it has the impacts on the guardianship for their minors. The assigning of guardianship can be reviewed by the judge on request of the father or mother based on the change in condition. The legal consequence for the guardianship annulment due to judicial technical mistake of the court in assigning the guardianship is the annulment of the guardianship belonged to the mother named Alda Winona Nurrahmadhani based on the Ruling No. 400/Pdt.G/2011/PN.Sby. The guardianship for the child is returned to both parents as the guardians for their underage child.Keywords: Guardianship, Minor, Divorce.